Should digital taxation be in sync with the OECD-G20 Two-Pillar Framework? An Analysis of the Equalization Levy in India and Its Aftermath. - Paul, Arun; Ramalingam, N (Gyan Management Journal, 2023)
The flourishing growth of the digital economy in India has made  digital taxation an indispensable system in India’s revenue generation.  The study provides a detailed assessment of the OECD (Organization  for Economic Cooperation and Development)- G20(Group of 20)  group’s initiatives on digital economy taxation. Furthermore, there is  an in-depth analysis of the limitations of the Indian ‘Income Tax Act  1961’ and the subsequent adoption of the equalization levy. The effect  of equalization levies on tax treaties, rules, and the General Agreement  on Trade in Services (GATS) are examined in detail. The economic  impact of the equalization levy is also evaluated by analyzing the  digital trade restrictiveness index. Finally, an evaluation is carried out  on the OECD- G20 Two-Pillar framework on the background of the  problems of digital taxation. The study also examines the growth of the  equalization levy in India and assesses the USTR (United States Trade  Representative) report in light of the equalization levy.
Keywords: Equalization Levy; Digital Taxation; Tax Treaties; Double Taxation; Two- pillar framework